Analytical study of the transport problem in the city of Constantine (North-East of Algeria) - Medjitna, Wafa (Technium Social Sciences Journal, 2023)
The problem of urban transport is considered to be one of the major concerns facing cities today; this situation is due to several factors, notably the lack of harmony and compatibility between spatial expansion, population growth and the development of road infrastructure in these cities, which are growing at a rate that exceeds that of the road network. The effects are multiple, congestion and traffic jams, pollution, economic and social impacts. Constantine, the third metropolis of Algeria and capital of the eastern region of the country, represents an ideal case to study the subject; given its physical and human geographical specificities, as well as the different interventions in terms of land use planning during the post-independence period. What we are going to approach through the present paper